The Digitalisation of Administrative Processes and Institutional Agility in SUCs Cebu City: The Mediating Role of Employee Digital Readiness - Bithay, Leovigilda L. (UI Scholars Hub, 2026)
Research Aims: This study examines how the digitalisation of administrative processes influences institutional agility in SUCs in Cebu City, Philippines, and explicitly investigates employee digital readiness as a mediating capability that translates digital investments into organisational adaptability. Design/Methodology/Approach: A quantitative predictive research design was employed using a structured survey administered to 300 administrative employees selected through purposive sampling. PLS-SEM was used to test direct and indirect relationships. Research Findings: The digitalisation of administrative processes has a significant positive effect on institutional agility. Employee digital readiness partially mediates this relationship, indicating that technological modernisation alone yields limited gains in agility unless supported by digitally competent and confident employees. Institutions with higher levels of employee digital readiness demonstrate greater adaptability, responsiveness, and service efficiency. Theoretical Contribution/Originality: This study empirically demonstrating how employee digital readiness functions as a dynamic capability that links process digitalisation to institutional agility. This research highlights the capability-building mechanism through which administrative digitalisation enhances organisational responsiveness in public higher education institutions. Managerial Implication in the South East Asian Context: The results underscore the need for SUC leaders, HR managers, and digital governance officers across Southeast Asia to complement administrative digitalisation initiatives with sustained investments in employee digital capacity building. Research Limitation & Implications: This study is limited to SUCs in Cebu City, which may limit its generalizability to other public institutions and national contexts. Future research may adopt comparative cross-regional designs or qualitative approaches.